Investigation of the volume effect on a simple batch fermentation process - P. Crooke (2018)
In this paper two models, one structured and the other unstructured, for the simple batch fermentation process, based on the kinetic scheme S+R ⇌k 1 k 2 C ⇀k 3 2R, are compared quantitatively and qualitatively. One model assumes that the volume of the cells in the fermentation process is approximately constant while the other model incorporates the changing cell volume. It is shown that the specific growth rates for each model differ by approximately a factor of 2. Qualitatively, the shape of the trajectories for each model in the specific growth rate-substrate phase plane are very similar. One model is the traditional fixed volume model where the intra- and extracellular substrate levels are equal, while the "new" model incorporates the intracellular substrate (without cellular transport) with changing cell volumes. © 1989.